The picture book and the inclusion of deaf children in the school library - Pereira, Ana Paula; Coneglian, André Luís Onório [UNESP]; Bortolin, Sueli [UNESP]; Alcará, Adriana Rosecler (FapUNIFESP (SciELO), 2021)
The objective of the article is to reflect on the reading and writing process of the deaf, showing its impact on the actions of the reading mediator in the school library and to present the picture book as an efficient resource for the reading flow of the deaf. He argues that deafness goes beyond the finding of a disability and stands out for a difference. In this sense, it was essential to address in this work the Sign Language, a space-motor-visual language that will mediate the thinking and communication of the deaf subject, as his thinking is processed differently from the listeners, that is, through signs. Methodological procedures, the text was built based on bibliographical research, in the areas of Education, Librarianship and Information Science, without temporal delimitation due to the scarcity of scientific production, especially in the last two areas. It emphasizes that the school library needs to value the reading of children's literature, which can be a source of diversity and multiplicity, and the action of reading mediators is essential to strengthen reading practices. Detects that, in general, a school library does not present itself as an accessible and inclusive place and, for this reason, it is not part of the life of the deaf; as well as the attitude of the mediators towards the deaf child does not strengthen the feeling of belonging and the appropriation of the various literary texts. It concludes that the picture book, with its visual receptive vocabulary, tends to contribute to the insertion of deaf children in the universe of reading and to favor enjoyment, pleasure and learning through literature.
O livro de imagem e a inclusão da criança surda na biblioteca escolar
Keywords: Accessible school library; Deaf reader; Picture book; Reading mediator